Prevalence and trends of low birth weight in Iran: A systematic review and - Nazari, Fatemeh; Vaisi, Zahra; Sayehmiri, Kourosh; Vaisani, Yousef; Esteki, Taraneh (Advances in Nursing & Midwifery, 2013)
ABSTRACT Introduction: Low birth weight (LBW) is defined as a weight of 2499 g or less and in world it is considered an important determinant of infant health status. This paper aims to determine of trends and prevalence of LBW in Iran with Meta analysis method. Materials and Methods: on the computerized literature valid on valid keyword with search in valid database (SID.MEDLIB, IRANMEDEX, GOOGLE, MAGIRAN, and PUBMED) recruited in different geographic areas. To explore heterogeneity in studies I 2 index was used. Meta-analysis used to data analysis with random effects model. Results: Hospital data 195075 children enrolled in study. The Thirty eight studies met our inclusion criteria. The pooled prevalence rate of LBW was 7%. Prevalence of LBW in Iran showed an increasing trend during 1991-2010. Conclusions: The LBW rate in Iran is high. There is a need to change obstetric policy on weight gain during pregnancy to reverse the LBW rate trend. Keywords: Low birth weight, Iran, Meta-analysis, Systematic Review 1. Student Research Committee, Ilam University of Medical Sciences, Ilam,Iran 2. Department of Social Medicine, faculty of Medicine, Ilam University of Medical Sciences, Ilam-Iran 3. Psychosocial Injuries Research Center, Ilam University of Medical Sciences 4. PhD candidate ,Faculty member Department of Basic sciences Faculty of Nursing and Midwifery Shahid Beheshti university of Medical sciences Tehran-Iran *Corresponding author:Sayehmiri@razi.tums.ac.ir